Sicily on the road. Emotional connections and motivation in an example of informal interpretive communication - Villagrá Terán, María Montserrat (Círculo de Lingüística Aplicada a la Comunicación, 2021)
The indissolubility of the tourism and culture binomial makes tourist communication appear to us as an inexhaustible source of cultural elements and Sicily, a cultural area that will occupy this space, represents a tourist destination highly appreciated by Spanish travelers who, before visiting the Island, seek information about it in tourist forums. The user of the forum, in turn, satisfies that informative requirement because he has already visited the place, performing a function of cultural mediator revealing the idiosyncrasy of the Italian Island and the places of greatest interest. As we are going to present in this study, the role played by this user of the forum is unsuspectedly related to the cultural mediation carried out by tourism professionals, who use similar media and strategies. These strategies are revealed especially in the motivating facet through the creation of emotional bonds. Specifically, we will analyze the limitation of technicalities, the creation of cultural bridges through reformulations, the use of cultural terms, the presence of stereotypes and the generation of personal meanings of respect and custody, elements that affect precisely that emotional facet of this curious example of informal mediated tourism communication